The QR code as a communication tool in cultural valorization: intercultural study between the cities of Bragança (Portugal) and Salvador (Brazil) - Gutierriz, Ives Emídio (2021)
This study aims to investigate, through the visitor's perception, the degree of adoption of the QR Code technology and how much it can contribute to keeping the local memory and culture alive. A quantitative research methodology has been adopted using an exploratory descriptive and inferential analysis of the data. Data has been collected using a non-probabilistic sample to which has been applied a questionnaire survey, in October and November 2019, under an intercultural study between the cities of Bragança (Portugal) and Salvador (Brazil). Out of the 503 respondents, 84.5% know the QR Code and 85.3% have already used this technology. Visitors demonstrate receptivity to the adoption of the QR Code ap-plied to culture by positively agreeing to use it for this purpose, even though the sample less frequently used it in tourist visits. It was found that the use of this technology can collaborate with the promotion of local tourism and social inclu-sion.